Sosialisasi Rainwater Harvesting (RWH) bagi Tim PKK Desa: Melangkah Menuju Desa Mandiri Air Bersih - Yuliani Wahyu Sardana (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
The need for clean water, which is still mostly still supplied by groundwater, if it is used continuously, can experience a clean water crisis, but on the contrary, surface water during the rainy season is very abundant so it needs to be utilized. The use of excess water during the rainy season can be used for various purposes when water is needed, especially supplies when experiencing a water crisis in the dry season. Rainwater is considered cheap in its use because rain must fall in every place so that it can be used directly both without and with the treatment process. The use of rainwater as a source of clean water is by Rainwater Harvesting technique. The purpose and benefits of the service carried out are to provide understanding to the PKK Mobilization Team related to Rainwater Harvesting (RWH) so that it is expected to be able to become a Village Initiator on a household scale to move towards a Clean Water Independent Village. The method is carried out by socialization using interactive material presentations and then discussions at the end of the session. A total of 91 participants from 26 villages who participated were able to receive socialization materials well and a detailed understanding which is evident from the enthusiasm of the participants in the discussion and question and answer sessions provided in the forum. This understanding can be a provision for the PKK mobilization team of each village as a Village Initiator on a household scale to realize an independent village with clean water.